COMPARISON EFFECT OF ACUPUNCTURE AND JUAN BI TANG IN FROZEN SHOULDER PATIENTS SURABAYA EAST JAVA - Anindini Winda Amalia; Wong Thea Sairine; Jessi Suryani Setiawan (Universitas Kusuma Husada Surakarta, 2026)
Background: Frozen shoulder is a musculoskeletal condition characterized by pain and restricted shoulder joint mobility. The purpose of this study was to evaluate how well acupuncture and Juan Bi Tang, a traditional Chinese herbal remedy, reduced shoulder pain and enhanced shoulder function in patients with frozen shoulder in Surabaya, East Java. Methods: 14 female patients with primary frozen shoulder caused by wind-cold-dampness syndrome were included in the pre-experimental design, which included a pretest and a post-test. One group of participants received acupuncture treatment for seven days in a row, while the other group received Juan Bi Tang decoction for the same amount of time. On days 0, 3, and 7, range of motion (ROM) tests were used to measure shoulder mobility, and the Visual Analogue Scale (VAS) was used to gauge the severity of the pain.Results: Following treatment, the VAS scores in both groups significantly decreased (p = 0.000), according to the results. While there was no discernible difference on day 7 (p = 0.778), the acupuncture group experienced a quicker decrease in pain on day 3 than the herbal group (p = 0.029). Both groups significantly improved their range of motion (p = 0.000), but the acupuncture group had better early results on day three (p = 0.005). Both treatments showed comparable gains by day 7 (p = 0.761). Conclusion: Patients with frozen shoulder found that both Juan Bi Tang and acupuncture helped to improve shoulder function and reduce pain. Herbal therapy showed a similar effect after one week, but acupuncture showed a quicker onset of improvement.